Diagnostic Accuracy of Placental Thickness in Lower Uterine Segment Measured by Ultrasound in Prediction of Placenta Accreta Spectrum in Patients with Placenta Previa. A Diagnostic Test Accuracy Study - Elmaraghy AM; Taha Fayed S; Abd ElHamid Ali M; Ali Hassanien M; Mohamed Mamdouh A (Dove Medical Press, 2023)
Ahmed Mohammed Elmaraghy,1 Salah Taha Fayed,1 Mahmoud Abd ElHamid Ali,2 Monira Ali Hassanien,3 Ahmed Mohamed Mamdouh1 1Department of Obstetrics & Gynecology, Faculty of Medicine, Ain Shams University, Cairo, Egypt; 2Department of Obstetrics & Gynecology, Bani Sweif Hospital, Ministry of Health, Bani Sweif, Egypt; 3Obstetrics and Gynecology, Ultrasound and Fetal Care Unit, Ain Shams University Maternity Hospital, Cairo, EgyptCorrespondence: Ahmed Mohammed Elmaraghy, Email amam85@outlook.comObjective: The aim of the study was to evaluate the association between placental thickness and placenta accreta spectrum (PAS) in patients with placenta previa.Materials and Methods: In this prospective study, 40 patients diagnosed with placenta previa were included. The maximum placental thickness in the lower uterine segment was obtained using a transabdominal scan. For the image to be deemed suitable, a midline sagittal section of the lower uterine segment (with the implanted placenta) and the cervical canal, with the intervening urinary bladder had been required. Intraoperative attendance was ensured for the detection of cases with spontaneous separation and cases with morbid adherence. All specimens removed were sent for histopathology to confirm PAS. The primary outcome of the study was to detect a threshold of placental thickness which can be used as a cut-off value in such screening test. The number of units of packed RBCs transfused during the operation and bladder injury were secondary measures of outcome.Results: Forty patients were included in the study; 20 patients were ultimately diagnosed with PAS while 20 patients did not have PAS. Mean placental thickness was significantly higher in the PAS patients compared with those with no invasive placentation (61.00 mm Vs 43.00 mm, P value 0.000). Using receiver operating characteristic (ROC) curve, a threshold placental thickness of 58mm was associated with 55% sensitivity, 90% specificity, 84.6% positive predictive value, and 66.7% negative predictive value. Multivariate logistic regression showed that placental thickness more than 58mm and having past history of more than three cesarean sections were independent risk factors for PAS among patients with placenta previa.Conclusion: Placental thickness in the lower uterine segment is increased in patients with placenta previa with PAS compared to those with no PAS. Such finding can be implemented into clinical practice by using placental thickness as a screening test for PAS in patients with placenta previa.ClinicalTrials.gov ID: NCT05500404.Keywords: placental thickness, placenta accreta spectrum, placenta previa, ultrasound, cesarean section